Environmental changes in Boeckella Lake, Antarctica Peninsula, between 1958 and 2023 - Petsch, Carina; Silva Busso, Adrián Angel (Investigaciones Geográficas: Una mirada desde el sur, 2024)
The Antarctic Peninsula (AP) has experienced rapid warming in recent years, which has caused permafrost degradation. In the north of AP, in Hope Bay, Boeckella Lake has experienced rapid and sudden drainage events in recent decades driven by thermokarst processes. The study aims to characterize environmental changes in Hope Bay, especially in Boeckella Lake between 1958 and 2023. Data generated in this research and from bibliographic sources on limnological and sedimentological characteristics; thaw water supply data; photographs; Remote Sensing; and bathymetry of Boeckella Lake were used. Remote Sensing data shows that on February 29, 1988, the lake had an area of 40,236 m2. Since 2010, Boeckella Lake has been divided into small lakes, recording an area of 20,408 m2 in 2023, a decrease of approximately 50%. Bathymetric data show that between 1993 and 2013 the lake increased in depth, due to the ground collapse. In addition, the high level of surface runoff in the area from the Buenos Aires glacier may contribute to an increase in organic and inorganic matter entering Boeckella Lake and other limnological changes. The Boeckella Lake has undergone significant changes over the years due to permafrost thaw and intensified thermokarst erosion, driven by the rising air temperatures observed in recent years. However, anthropogenic interferences strongly affect the lake dynamics.